Undergraduate nursing students' experience of clinical supervision - Gabieba Donough; Marianna van der Heever (AOSIS, 2018)
Background: Clinical supervision plays a major role in the undergraduate nursing programme. There have been some local studies addressing clinical supervision; however, there still remains a lack of knowledge and understanding how to improve quality supervision of undergraduate nursing students. This article is based on the authors' original thesis. Objectives: The objective of the study was to explore the experiences of undergraduate nursing students on clinical supervision. Method: A descriptive design with a qualitative approach using focus group interviews was used to explore the experiences of undergraduate nursing students regarding clinical supervision. Purposive sampling was used for selection of 36 participants. The participants needed to be enrolled at the institution under study, at the time of the study, as undergraduate nursing students in order to meet the inclusion criteria. The participants also needed to have worked at clinical facilities where they received clinical supervision. Nine (n = 9) students were purposively selected from each year level to participate in focus group interviews. The interviews were analysed using content analysis. Results: The findings indicated both positive and negative experiences regarding clinical supervision. The results were tabulated in which the positive experiences were grouped together and were separated from the negative experiences of the undergraduate students. Positive experiences included the support that was received from supervisors. These were, however, overshadowed by many comments on negative experiences concerning the behaviour and competencies of the supervisors. The findings also confirmed that the students experienced differences in the clinical procedures demonstrated by various supervisors. Negative experiences that relate to abusive behaviour such as misuse of power were also found, as well the incongruence amongst clinical supervisors regarding clinical procedures. Recommendations were proposed to enhance clinical supervision and the learning experiences of student nurses. Conclusion: The study findings suggest a need for continuous professional development for clinical supervisors by means of in-service training as well as to maintain congruence by clinical supervisors when demonstrating clinical procedures.